Relational Student Engagement in Co-curricular Spaces: Evidence from a South African University (Journal of Student Affairs in Africa, 2022)
Student engagement is a widely researched and utilized concept to enhance student experiences and outcomes. Most research on student engagement, however, focuses on curricular engagement with relatively little emphasis placed on the co-curriculum. This study utilizes Case’s theory of relational engagement to analyse findings from three focus groups conducted at a university in South Africa to better understand how relational engagement is instantiated in the co curriculum and how the co-curriculum differs from the standard academic curriculum in terms of engagement. In particular, we show relational engagement is just as important in the co-curriculum, highlighting student relations to broader university life, to fellow students, and to communities beyond the campus.